2006
DOI: 10.1200/jco.2005.03.8810
|View full text |Cite
|
Sign up to set email alerts
|

Association of Activated Transcription Factor Nuclear Factor κB With Chemoradiation Resistance and Poor Outcome in Esophageal Carcinoma

Abstract: Our data suggest that esophageal cancers with activated NF-kappaB have aggressive clinical biology and poor treatment outcome. Additional understanding of NF-kappaB regulated pathways may uncover potential therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 39 publications
3
100
0
1
Order By: Relevance
“…More recently, constitutively active NF-kB activation has also been found in cancer patients and shown to correlate with prognosis of the disease (Buchholz et al, 2005;Izzo et al, 2006). Work from our laboratory and others have shown that NF-kB is constitutively active in head and neck squamous cell carcinoma (HNSCC) Aggarwal et al, 2004), and play a critical role in the proliferation of the tumor cells LoTempio et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…More recently, constitutively active NF-kB activation has also been found in cancer patients and shown to correlate with prognosis of the disease (Buchholz et al, 2005;Izzo et al, 2006). Work from our laboratory and others have shown that NF-kB is constitutively active in head and neck squamous cell carcinoma (HNSCC) Aggarwal et al, 2004), and play a critical role in the proliferation of the tumor cells LoTempio et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…NF-κB is a protein complex composed of multiple subunits, including p50, p52, ralA (p65), ralB and c-rel. It is retained in an inactive form in the cytoplasm by its interaction with IκB (4,12). extrinsic stimuli such as tNFα cause phosphorylation of IκB and its subsequent ubiquitination and degradation by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy of 5-FU and NF-κB sirNA was effective in esCCs, providing further evidence that NF-κB is associated with the sensitivity of 5-FU. a gene expression profiling study previously identified high expression levels of key regulatory genes in the NF-κB pathway, including trAF2, an inhibitor of NF-κB kinase, and RalB in chemoresistant cancer (12). Moreover, curcumin inhibited NF-κB activity and sensitized cancer cells to antiproliferative agents, such as 5-FU or cisplatin (23).…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…First, NFκB has been related to cell transformation. 21 Second, NFκB is constitutively active in tissues of many cancers [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 2). Third, activation of inflammatory pathway is mediated through NFκB in response to lifestyle-related factors such as tobacco, stress, dietary agents, obesity, alcohol, infectious agents, irradiation and environmental stimuli, which account for as much as 95% of all cancers.…”
Section: Introductionmentioning
confidence: 99%